2021
DOI: 10.3389/fpsyg.2021.660796
|View full text |Cite
|
Sign up to set email alerts
|

Human Ratings of Writing Quality Capture Features of Syntactic Variety and Transformation in Chinese EFL Learners’ Argumentative Writing

Abstract: Traditionally, writing quality is measured by human ratings, either holistically or analytically. The present study aimed to investigate the locus of human ratings by analyzing the linguistic features that are predictive of writing quality. One hundred and 44 argumentative writing samples from Chinese learners of English as a foreign language were evaluated by human ratings and quantitative measurement of writing quality indexed by Coh-Metrix. Holistic and analytic human ratings had significant correlations wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Research on writing quality has gained importance in recent years, giving prominence to the correlation between linguistic features and overall writing quality (Austin, 2020;Casal & Lee, 2019;Crossley, 2020;Nagy & Beers, 2007;Noblesa & Paganucci, 2015;Stevenson & Phakiti, 2014;Wahyuni, 2017;Xue, et al, 2021;Yoon, 2018). Austin (2020) highlighted the fact that the quality of writing basically lies in the appropriate selection of vocabulary that enlightens the meaning intended by the writer.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Research on writing quality has gained importance in recent years, giving prominence to the correlation between linguistic features and overall writing quality (Austin, 2020;Casal & Lee, 2019;Crossley, 2020;Nagy & Beers, 2007;Noblesa & Paganucci, 2015;Stevenson & Phakiti, 2014;Wahyuni, 2017;Xue, et al, 2021;Yoon, 2018). Austin (2020) highlighted the fact that the quality of writing basically lies in the appropriate selection of vocabulary that enlightens the meaning intended by the writer.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A growing research has begun to focus on EFL writing quality referring to the factors contributing to its development (Casal & Lee, 2019;Kent & Wanzek, 2016;Noblesa & Paganucci, 2015;Wahyuni, 2017;Xue, et al, 2021;Yoon, 2018). In a recent research, Alotaibi (2015) identified two significant factors influencing writing quality pertaining to lexical cohesion; using the same type of the lexical item, and the lexical item location.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence suggests that complexity measures do not only index L2 writing quality, but also L2 writing development and L2 proficiency. A growing number of studies have revealed the ability of complexity measures to distinguish between low-rated and high-rated papers [8][9][10][11][12][13][14][15]. Other studies have shown that complexity measures can be reliable indices of L2 writing development over time e.g., [16,17], c.f., [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%